Forms of address as Cross-Cultural Code-Switching: The case of German and Danish in Higher Education - Ørsnes, Bjarne (Linguistik Online, 2016)
Both German and Danish have distinct pronouns for addressing communication partners formally and informally (referred to as V for Sie/De and T for du/du). However, their use differs considerably in Germany and Denmark, e. g. in higher education. In Germany, the lecturer and the students use V, in Denmark they use T. Based on the observation that Danish students are very reluctant (and sometimes even opposed) to use V in the classroom in Denmark, this article proposes to consider the use of V and T as a case of Cross-Cultural Code-Switching. It is hypothesized that V causes Cultural Cognitive Dissonance for (young) Danes since V is interpreted as an overt manifestation of power distance in a society which considers itself as egalitarian. Ways to cope with such cognitive dissonance in foreign language teaching are discussed. Furthermore, the article addresses the broader question of when cultural behaviours are supposed to apply and – in particular – what conventions are appropriate in higher education in Denmark when German is the language of instruction: should we use V as in Germany or T as in Denmark? Arguments for both choices are presented and discussed.